Minimally-invasive and non-invasive methods of thermal destruction in the treatment of patients with aggressive fibromatosis - L. I. Moskvicheva (Сибирский онкологический журнал, 2023)
The purpose of the study was to characterize various methods of local physical destruction used in the treatment of patients with aggressive fibromatosis and demonstrate international experience of their use.Material and Methods. literature search was conducted in the electronic databases Rsci (Russian science citation index) and NcBi (National centre for Biotechnology information) in the interval time between 2002 and 2022. The review was devoted to the thermal ablation modalities (radiofrequency, microwave ablation, cryodestruction, high-intensity focused ultrasound ablations) used in therapy of patients with desmoid fibromas of various locations, as well as their safety and efficacy.Results. The review presents the current data on safety and efficacy of minimally-invasive and non-invasive methods of hypo- and hyperthermic local destruction in patients with aggressive fibromatosis, gives the characteristics of exposure and biological effects when performing radiofrequency and microwave ablation, cryodestruction, high-intensity focused ultrasound therapy, describes the main limitations of the methods, indications and contraindications for their application, as well as the methods of prevention of the development of desmoid fibromas.Conclusion. The described methods of local destruction are used in clinical practice mainly for palliative and symptomatic purposes, in case of persistent tumor growth or recurrence, ineffectiveness of other treatment options or contraindications to them due to concomitant somatic pathology or functional status of the patient. Inclusion of these methods in the treatment plan of patients with aggressive fibromatosis can contribute to the reduction of pain syndrome, improvement of functional status of patients as well as long survival with no evidence of tumor progression.